Impact of tree species replacement on carbon stocks in forest floor and mineral soil - Fonseca, Felícia (2011)
This study aims at evaluating the influence of replacing areas of Quercus pyrenaica, which represents native vegetation of Serra da Nogueira, NE of Portugal, by Pseudotsuga menziesii on carbon stocks in forest floor and mineral soil. Three sampling areas were selected in adjacent locations with similar soil and climate conditions. The first area, covered by Quercus pyrenaica (QP), represents the original soil. The second area is in a 40 years old stand of Pseudotsuga menziesii (PM40), and the third one, also under Pseudotsuga menziesii, is 15 years old (PM15). In each sampling area, at 10 randomly selected points, samples were collected in the forest floor (0.49 m2 quadrat) and in the soil (at 0-5, 5-10 and 10-20 cm depth). The forest floor stores 17, 13 and 6% of total carbon for PM40, PM15 and QP, respectively. Four decades after species replacement, a soil organic carbon loss is observed, although no significant differences were found when comparing soil under introduced (PM) with original species (QP). A carbon loss of around 30%, in PM15, and gains of about 10%, in PM40, are computed when considering mineral soil and forest floor together.